Exploring the potential of Bacillus for crop productivity and sustainable solution for combating rice false smut disease - Pandey, Neha; Vaishnav, Richa; Rajavat, Asha Singh; Singh, Arvind Nath; Kumar, Sanjay; Tripathi, Ravi Mani; Kumar, Madan; Shrivastava, Neeraj (Frontiers in Microbiology, 2024)
Rice false smut, which is caused by the soil-borne fungal pathogen Ustilaginoidea virens (U. virens), is one of the most threatening diseases in most of the rice-growing countries including India that causes 0.5–75% yield loss, low seed germination, and a reduction in seed quality. The assessment of yield loss helps to understand the relevance of disease severity and facilitates the implementation of appropriate management strategies. This study aimed to mitigate biotic stress in rice by employing a rhizobacterial-based bioformulation, which possesses diverse capabilities as both a plant growth promoter and a biocontrol agent against U. virens. Rhizobacteria were isolated from the soil of the rice rhizospheres from the healthy plant of the false smut affected zone. Furthermore, they were identified as Bacillus strains: B. subtilis (BR_4), B. licheniformis (BU_7), B. licheniformis (BU_8), and B. vallismortis (KU_7) via sequencing. Isolates were screened for their biocontrol potential against U. virens under in vitro conditions. The antagonistic study revealed that B. vallismortis (KU_7) inhibited U. virens the most (44.6%), followed by B. subtilis BR_4 (41.4%), B. licheniformis BU_7 (39.8%), and B. licheniformis BU_8 (43.5%). Various biochemical and plant growth promoting attributes, such as phosphate and Zn solubilization, IAA, ammonium, siderophore, and chitinase production, were also investigated for all the selected isolates. Furthermore, the potential of the isolates was tested in both in vitro and field conditions by employing talc-based bioformulation through bio-priming and root treatment. The application of bioformulation revealed a 20% decrease in disease incidence in plants treated with B. vallismortis (KU_7), a 60.5% increase in the biological yield, and a 45% increase in the grain yield. This eco-friendly approach not only controlled the disease but also improved the grain quality and reduced the chaffiness.